Potential biomarkers on gametogenesis process and in sperm quality of european EEL (Anguilla anguilla) - Leonardo, Ana Margarida Assis (2016)
Dissertação de mestrado, Aquacultura, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015